Moderator role of gender in the effect of nomophobia on digital game addiction - Çınar Özbay, Sevil; Durmuş Sarıkahya, Selma; Özbay, Özkan; Akçam, Aysun; Kanbay, Yalçın (Journal of Dependence, 2023)
Objective: The aim of the study was to investigate the effect of nomophobia on digital game addiction and to examine the moderator role of gender variable on this effect. Method: Associate or undergraduate level university students constituted the study population. The sample consisted of 1074 of these students who stated that they played digital games. “Student Information Form”, “Fırat Nomophobia Scale” and “Digital Game Addiction Scale” were used as data collection tools. Results: The students with various socio-economic status consisted of 60.7% female, and the mean age was 21.5 ± 2.9 (Min=17; Max=38) years. Based on the findings, nomophobia was determined to have an effect on digital game addiction. Gender variable displayed a moderation effect, more prominent in male gender with respect to female gender. In addition, it was determined in the study that nomophobia explained approximately 16% of the change in the digital internet addiction variable. Conclusion: The effect of male gender on the effect of nomophobia on digital game addiction is greater than the female gender. Regular evaluation of srudents’ nomophobia and digital game addiction levels is recommended to determine the factors that affect them in detail.